Alloy-loaded conductive aerogel catalyst as well as preparation method and application thereof
By using conductive aerogel TiO2 support to support RuIr alloys in PEM water electrolytic anode, the RuIr/TiO2 composite materials are formed, which solves the problems of high cost and low efficiency of existing oxidation catalysts, and achieves efficient and stable electrochemical water decomposition reactions.
Patent Information
- Application Number
- CN202411750047.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-11
AI Technical Summary
In the existing electrochemical water decomposition technology, the high cost and low efficiency of oxidation catalysts limit the efficiency of hydrogen production, especially the slow kinetics of oxygen evolution reaction (OER) and high energy is required to overcome the reaction energy barrier.
After using conductive aerogel TiO2 as the matrix, after impregnating the precursor supported by Ru and Ir, RuIr/TiO2 composite material is formed by calcining, as PEM water electrolytic anode material, reducing the amount of precious metals and improving the stability and activity of the catalyst.
By using a porous, high specific surface area and conductive TiO2 aerogel support, the high dispersion of RuIr nanoparticles is achieved, the reaction area of the catalyst is expanded, the amount of precious metals is reduced, the activity and stability of the catalyst is improved, and the local overpotential of the electrolytic water anode is reduced.
Smart Images

Figure CN119593014A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemistry, and in particular relates to an alloy-loaded conductive aerogel catalyst and a preparation method and application thereof. Background Art
[0002] The serious energy crisis and environmental problems have prompted the development of renewable energy storage and conversion. Hydrogen, as a clean and pollution-free renewable energy carrier, is expected to solve energy and environmental problems. Electrochemical water splitting is one of the most efficient and clean hydrogen production technologies. Among them, the oxygen evolution reaction (OER) has slow reaction kinetics and transmits 4e - , high energy is required to overcome the reaction energy barrier, which is the bottleneck reaction that restricts the efficiency of electrochemical water splitting. Among various catalysts, precious metals Ir and Ru are considered to be the best catalysts for OER, and their properties in the anode of proton exchange membrane water electrolyzer (PEMWE) are unmatched by other materials. However, their high cost and scarcity greatly limit their widespread application. Therefore, it is imperative to develop catalysts with low precious metal dosage, and it is necessary to consider how to improve their atomic economy. Summary of the invention
[0003] The purpose of the present invention is to overcome the deficiencies in the prior art and provide an alloy-loaded conductive aerogel catalyst and a preparation method and application thereof. The catalyst of the present invention is suitable for PEM water electrolysis anode materials, with a conductive high specific surface area aerogel TiO2 as a matrix, after impregnation with Ru and Ir loaded precursors, a RuIr / TiO2 composite material is formed by calcination. Compared with general iridium oxide catalysts, this catalyst uses a porous, high specific surface area and conductive material as a carrier, which reduces the amount of precious metals used. At the same time, the alloy material changes the coordination environment of the metal active center, improves the stability and activity of the catalyst, and can further reduce the local overpotential of the electrolytic water anode.
[0004] In order to achieve the above technical objectives, the technical solution adopted by the embodiment of the present invention is:
[0005] In a first aspect, an embodiment of the present invention provides an alloy-loaded conductive aerogel catalyst, comprising a substrate and a precious metal loaded on the substrate, wherein the substrate adopts conductive aerogel, the loading mass ratio of the precious metal on the substrate is 1-20%, the precious metal comprises precious metal A and precious metal B, and the molar ratio of the precious metal A to the precious metal B is 1-9:1; the precious metal A is Ir, and the precious metal B comprises one or more of Ru, Pt and Rh.
[0006] In a second aspect, an embodiment of the present invention provides a method for preparing the alloy-supported conductive aerogel catalyst according to the first aspect, comprising the following steps:
[0007] Step S1, dissolving a precursor of precious metal A and a precursor of precious metal B in ethanol, then adding a sodium citrate solution to the mixture, and ultrasonically treating the obtained solution to obtain a solution Y1;
[0008] Step S2, immersing the conductive aerogel in the solution Y1, then heating and evaporating all the solvent to obtain a wet gel, transferring the obtained wet gel to a porcelain boat, placing it in a tubular furnace, and calcining it at a heating rate of 3-8°C / min in a hydrogen-argon mixed atmosphere, and collecting the obtained black product;
[0009] Step S3, removal of impurity ions: centrifugally washing the black product obtained in step S2 with deionized water until the conductivity of the washing water is lower than 5 μS / m, so as to remove excess impurity ions;
[0010] Step S4, catalyst drying: the solid sample washed in step S3 is placed in a vacuum drying oven at 50-80° C. and heated for 12-24 hours to obtain a finished catalyst.
[0011] Furthermore, in step S2, the conductive aerogel includes one of TiO2 aerogel, graphene aerogel and biomass carbon aerogel.
[0012] Furthermore, the ultrasonic treatment time in step S1 is 10-30 minutes, and the ultrasonic power is 800-1000W;
[0013] The sodium citrate solution is dissolved and diluted at 2-10 times the weight of the sodium citrate solid, and the ratio of sodium citrate solid added is 10-15 times the total weight of the precious metal compound precursor.
[0014] Furthermore, in step S2, the conductive aerogel is immersed in solution Y1 for 6-24 hours; the temperature for heating to evaporate the solvent is 70-90°C, and the heating time is 4-8 hours; the heating temperature of the tubular furnace during calcination is 300-500°C, and the heating time is 2-6 hours.
[0015] Furthermore, the preparation of the TiO2 aerogel comprises the following steps:
[0016] (1) tetrabutyl titanate Ti(OBu)4, ethanol EtOH and glacial acetic acid CH3COOH are uniformly mixed in a molar ratio of 1:5-15:0.2-1 to form a solution Y2;
[0017] (2) mixing H2O, EtOH and CH3COOH in a molar ratio of 1-5:2-10:1 to form a solution Y3;
[0018] (3) slowly adding solution Y2 to solution Y3 at a rate of 0.5-2 mL / min, with the volume ratio of solution Y2:solution Y3 being 0.5-2:1;
[0019] (4) adding formamide DMF to the mixed solution obtained in step (3), wherein the molar ratio of Ti(OBu)4 to DMF is 1:0.01-0.2, stirring, and placing in a water bath at a constant temperature to obtain a TiO2 wet gel, and further condensing the obtained TiO2 wet gel at room temperature;
[0020] (5) Solvent replacement process of gel: the gel condensed in step (4) is placed in a water bath, during which EtOH is replaced, the gel is taken out and immersed in a mixed solution of EtOH and tetraethyl silicate (TEOS) for surface modification, and then the gel is immersed in n-hexane to replace the solvent and unreacted products in the gel;
[0021] (6) The gel is transferred into a beaker, which is wrapped with tin foil and dried in a drying oven at normal pressure using a gradient temperature increase system. After cooling, the TiO2 aerogel is obtained.
[0022] Furthermore, in step (4), the stirring time is 10-60 minutes, the temperature of the water bath is 20-40° C., the constant temperature standing time is 1-6 hours, and the further condensation time is 6-24 hours.
[0023] Furthermore, the temperature of the water bath in step (5) is 30-50°C, the gel is placed in the water bath for 12-36 hours, the number of ethanol replacements is 3-5 times, the volume ratio of EtOH to TEOS during replacement is 1:2-5, the water bath heating temperature range is 50-80°C, and the immersion time is 6-24 hours.
[0024] Furthermore, the gradient temperature rise system in step (6) is 50°C, 80°C, 100°C, 120°C, 140°C and 160°C, with each temperature maintained for 30-60 minutes.
[0025] In a third aspect, an embodiment of the present invention provides a use of the alloy-supported conductive aerogel catalyst described in the first aspect, wherein the catalyst is used as an anode catalyst for electrolyzing water to electrolyze water.
[0026] The technical solution provided by the embodiment of the present invention has the following beneficial effects:
[0027] (1) The electrolytic water anode catalyst of the present invention improves the preparation process of the existing iridium-based catalyst. The electrolytic water anode catalyst of the present invention still uses the precious metal Ir as the main alloy element for the selection, and uses aerogel as the matrix to achieve high dispersion of RuIr nanoparticles loaded on the matrix. The high specific surface area of the aerogel expands the reaction area of the catalyst. A large number of defects / vacancies can promote the electrocatalytic reaction, and a small amount of loaded alloy is achieved while promoting electron transfer between interfaces, which can reduce the amount of precious metal used, thereby reducing the catalyst cost and improving the activity of the catalyst.
[0028] (2) The TiO2 aerogel used as the matrix of the anode catalyst for electrolysis of water of the present invention is acid-resistant and can inhibit the agglomeration of precious metal nanoparticles. At the same time, the rutile phase obtained after high-temperature calcination is also conductive, which is beneficial to the transfer of electrons between catalysts and the stable operation of the electrolysis reaction.
[0029] (3) The electrolytic water anode catalyst of the present invention forms an alloy, changes the coordination environment of the metal active center, adjusts the electronic structure, affects the binding energy between the intermediate and the active center, forms a stable catalyst structure and improves the electrochemical performance of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a scanning electron microscope image of the TiO2 aerogel prepared in Example 1.
[0031] Figure 2 This is a scanning electron microscope image of the RuIr / TiO2 composite material prepared in Example 1.
[0032] Figure 3 It is the X-ray diffraction pattern of the catalysts prepared in Example 1 and Comparative Examples 1-2.
[0033] Figure 4 It is a comparison chart of the linear voltammetric electrochemical performance of the catalysts prepared in Example 1 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0035] Example 1
[0036] A method for preparing an alloy-supported conductive aerogel catalyst comprises the following steps:
[0037] (1) Ti(OBu)4, EtOH and CH3COOH were mixed uniformly in a molar ratio of 1:10.5:0.5 to form a solution Y2;
[0038] (2) H2O, EtOH and CH3COOH were mixed uniformly in a molar ratio of 2:5.25:1 to form a solution Y3;
[0039] (3) Solution Y2 was slowly added to solution Y3 at a drop rate of 1 mL / min, and the volume ratio of solution Y2:solution Y3 was 1.25:1;
[0040] (4) Add an appropriate amount of DMF to the above mixed solution, the molar ratio of Ti(OBu)4 to DMF is 1:0.09, stir for 30 minutes, and place in a water bath at 35°C for 2 hours to obtain TiO2 wet gel, and further condense the TiO2 wet gel at room temperature for 12 hours;
[0041] (5) Solvent replacement process of gel: All gels were placed in a 40°C water bath for 24 hours, during which EtOH was replaced three times. The gels were taken out and immersed in a mixed solution of EtOH and TEOS at 60°C for 12 hours for surface modification. The gels were then immersed in n-hexane to replace the solvent and unreacted products in the gel. The volume ratio of EtOH to TEOS was 1:3, and the volume proportion of TEOS was 75 vol%.
[0042] (6) The gel is transferred into a beaker, which is wrapped with tin foil and dried in a drying oven at normal pressure. The drying conditions are 50° C., 80° C., 100° C., 120° C., 140° C. and 160° C. for 30 minutes, respectively, to obtain TiO2 aerogel;
[0043] (7) 0.5 mmol of chloroiridic acid hexahydrate and 0.9 mmol of RuCl3·3H2O were dissolved in 5 mL of ethanol, and then 5 g of sodium citrate and 10 mL of water were added to the mixture. The resulting solution was ultrasonically treated for 10 min at an ultrasonic power of 1000 W to obtain a brown-red uniform solution Y1;
[0044] (8) 1.0 g of TiO2 aerogel was immersed in solution Y1 for 12 hours, and then kept at 80°C for 6 hours to evaporate all the solvents to obtain a wet gel. The obtained precursor was transferred to a porcelain boat and calcined in a tubular furnace at 400°C for 3 hours at a heating rate of 5°C / min under air atmosphere. The obtained black product was collected;
[0045] (9) Removal of impurity ions: washing the black product obtained in step (8) with deionized water until the conductivity of the washing water is less than 5 μS / m to remove excess impurity ions;
[0046] (10) Catalyst drying: The solid sample of step (9) was placed in a vacuum drying oven at 80° C. and heated for 12 h to obtain a finished catalyst, denoted as RuIr / TiO2, wherein the total mass content of the noble metal RuIr alloy in the catalyst was 15.75%.
[0047] Example 2
[0048] A method for preparing an alloy-supported conductive aerogel catalyst comprises the following steps:
[0049] (1) Ti(OBu)4, EtOH and CH3COOH were mixed uniformly in a molar ratio of 1:10.5:0.5 to form a solution Y2;
[0050] (2) H2O, EtOH and CH3COOH were mixed uniformly in a molar ratio of 2:5.25:1 to form a solution Y3;
[0051] (3) Solution Y2 was slowly added to solution Y3 at a drop rate of 1 mL / min, and the volume ratio of solution Y2:solution Y3 was 1.25:1;
[0052] (4) Add an appropriate amount of DMF to the above mixed solution, the molar ratio of Ti(OBu)4 to DMF is 1:0.09, stir for 30 minutes, and place in a water bath at 35°C for 2 hours to obtain TiO2 wet gel, and further condense the TiO2 wet gel at room temperature for 12 hours;
[0053] (5) Solvent replacement process of gel: All gels were placed in a 40°C water bath for 24 hours, during which EtOH was replaced three times. The gels were taken out and immersed in a mixed solution of EtOH / TEOS at 60°C for 12 hours for surface modification. The gels were then immersed in n-hexane to replace the solvent and unreacted products in the gel; the volume ratio of EtOH to TEOS was 1:3, and the volume proportion of TEOS was 75 vol%.
[0054] (6) The gel is transferred into a beaker, which is wrapped with tin foil and dried in a drying oven at normal pressure. The drying conditions are 50° C., 80° C., 100° C., 120° C., 140° C. and 160° C. for 30 minutes, respectively, to obtain TiO2 aerogel;
[0055] (7) 0.5 mmol of chloroiridic acid hexahydrate and 0.095 mmol of RuCl3·3H2O were dissolved in 5 mL of ethanol, and then 3 g of sodium citrate and 10 mL of water were added to the mixture. The resulting solution was ultrasonically treated for 10 min at an ultrasonic power of 1000 W to obtain a brown-red uniform solution Y1;
[0056] (8) 1.0 g of TiO2 aerogel was immersed in solution Y1 for 12 h, then kept at 80 °C for 6 h, all solvents were evaporated to obtain a wet gel, the obtained precursor was transferred to a porcelain boat, and calcined in a tubular furnace at 400 °C for 3 h at a heating rate of 5 °C / min under air atmosphere, and the obtained black product was collected;
[0057] (9) Removal of impurity ions: washing the black product obtained in step (8) with deionized water until the conductivity of the washing water is less than 5 μS / m to remove excess impurity ions;
[0058] (10) Catalyst drying: The solid sample of step (9) was placed in a vacuum drying oven at 80° C. and heated for 12 h to obtain a finished catalyst, which was recorded as Ru 0.1 Ir 0.9 / TiO2, where the precious metal Ru in the catalyst 0.1 Ir 0.9 The total mass content of the alloy is 9.56%.
[0059] Example 3
[0060] A method for preparing an alloy-supported conductive aerogel catalyst comprises the following steps:
[0061] (1) Ti(OBu)4, EtOH and CH3COOH were mixed uniformly in a molar ratio of 1:10.5:0.5 to form a solution Y2;
[0062] (2) H2O, EtOH and CH3COOH were mixed uniformly in a molar ratio of 2:5.25:1 to form a solution Y3;
[0063] (3) Solution Y2 was slowly added to solution Y3 at a drop rate of 1 mL / min, and the volume ratio of solution Y2:solution Y3 was 1.25:1;
[0064] (4) Add an appropriate amount of DMF to the above mixed solution, the molar ratio of Ti(OBu)4 to DMF is 1:0.09, stir for 30 minutes, and place in a water bath at 35°C for 2 hours to obtain TiO2 wet gel, and further condense the TiO2 wet gel at room temperature for 12 hours;
[0065] (5) Solvent replacement process of gel: All gels were placed in a 40°C water bath for 24 hours, during which EtOH was replaced three times. The gels were taken out and immersed in a mixed solution of EtOH / TEOS at 60°C for 12 hours for surface modification. The gels were then immersed in n-hexane to replace the solvent and unreacted products in the gel; the volume ratio of EtOH to TEOS was 1:3, and the volume proportion of TEOS was 75 vol%.
[0066] (6) The gel is transferred into a beaker, which is wrapped with tin foil and dried in a drying oven at normal pressure. The drying conditions are 50° C., 80° C., 100° C., 120° C., 140° C. and 160° C. for 30 minutes, respectively, to obtain TiO2 aerogel;
[0067] (7) 0.05 mmol of chloroiridic acid hexahydrate and 0.9 mmol of RuCl3·3H2O were dissolved in 5 mL of ethanol, and then 2.5 g of sodium citrate and 10 mL of water were added to the mixture. The resulting solution was ultrasonically treated for 10 min at an ultrasonic power of 1000 W to obtain a brown-red uniform solution Y1;
[0068] (8) 1.0 g of TiO2 aerogel was immersed in solution Y1 for 12 hours, and then kept at 80°C for 6 hours to evaporate all the solvents to obtain a wet gel. The obtained precursor was transferred to a porcelain boat and calcined in a tubular furnace at 400°C for 3 hours at a heating rate of 5°C / min under air atmosphere. The obtained black product was collected;
[0069] (9) Removal of impurity ions: washing the black product obtained in step (8) with deionized water until the conductivity of the washing water is less than 5 μS / m to remove excess impurity ions;
[0070] (10) Catalyst drying: The solid sample of step (9) was placed in a vacuum drying oven at 80° C. and heated for 12 h to obtain a finished catalyst, which was recorded as Ru 0.9 Ir 0.1 / TiO2, where the precious metal Ru in the catalyst 0.9 Ir 0.1 The total mass content of the alloy is 10.06%.
[0071] Comparative Example 1
[0072] The preparation method of RuIr alloy comprises the following steps:
[0073] (1) 0.5 mmol of chloroiridic acid hexahydrate and 0.9 mmol of RuCl3·3H2O were dissolved in 5 mL of ethanol, and then 5 g of sodium citrate and 10 mL of water were added to the mixture. The resulting solution was ultrasonically treated for 10 minutes at an ultrasonic power of 1000 W to obtain a brown-red uniform solution Y1;
[0074] (2) Solution Y1 was maintained at 80°C for 6 hours to evaporate all the solvent to obtain a brown solid. The obtained solid was transferred to a porcelain boat and annealed in a tube furnace at 400°C for 3 hours at a heating rate of 5°C / min under air atmosphere. The obtained black product was collected.
[0075] (3) Removal of impurity ions: Wash the solid sample obtained in step (2) with a large amount of deionized water, wherein the conductivity of the washing water is required to be less than 5 μS / m, so as to remove excess impurity ions;
[0076] (4) Catalyst drying: The solid sample of step (3) was placed in a vacuum drying oven at 80° C. and heated for 12 hours to obtain a finished catalyst, which was denoted as RuIr alloy, wherein the Ru / Ir mass ratio of the precious metal RuIr alloy in the catalyst was 1:1.
[0077] Comparative Example 2
[0078] The preparation method of TiO2 aerogel comprises the following steps:
[0079] (1) Ti(OBu)4, EtOH and CH3COOH were mixed uniformly in a molar ratio of 1:10.5:0.5 to form a solution Y2;
[0080] (2) H2O, EtOH and CH3COOH were mixed uniformly in a molar ratio of 2:5.25:1 to form a solution Y3;
[0081] (3) Solution Y2 was slowly added to solution Y3 at a drop rate of 1 ml / min, and the volume ratio of solution Y2:solution Y3 was 1.25:1;
[0082] (4) Adding an appropriate amount of formamide (DMF) to the above mixed solution, the molar ratio of Ti(OBu)4 to DMF is 1:0.09, stirring for 30 minutes, and placing it in a water bath at a constant temperature of 35°C for 2 hours to obtain TiO2 wet gel; the obtained gel is further condensed at room temperature for 12 hours;
[0083] (5) Solvent replacement process of gel: All gels were placed in a 40°C water bath for 24 hours, during which EtOH was replaced three times. The gels were taken out and immersed in an EtOH / TEOS mixed solution at 60°C for 12 hours for surface modification. The gels were then immersed in n-hexane to replace the solvent and unreacted products in the gels. The volume ratio of EtOH to TEOS in the EtOH / TEOS mixed solution was 1:3, of which the volume ratio of TEOS was 75 vol%.
[0084] (6) The gel is transferred into a beaker, which is wrapped with tin foil and dried in a drying oven at normal pressure. The drying conditions are 50° C., 80° C., 100° C., 120° C., 140° C. and 160° C. for 30 minutes respectively. The obtained catalyst is TiO2 aerogel.
[0085] (7) The TiO2 aerogel was calcined in an air atmosphere at 500°C in a tubular furnace at a heating rate of 5°C / min for 1 hour to obtain a rutile TiO2 aerogel.
[0086] Figure 1 This is a scanning electron microscope image of the TiO2 aerogel obtained under the atmospheric pressure calcination system in Example 1. It can be seen that the aerogel structure itself has a rich pore structure. Figure 2 This is a scanning electron microscope image of the RuIr / TiO2 composite material obtained after high-temperature calcination in Example 1. The pores of the aerogel after sintering will partially collapse and agglomerate, but compared with general TiO2 materials, it is still porous and has a high specific surface area. Figure 3 The X-ray diffraction patterns of the catalysts obtained in Example 1 and Comparative Examples 1-2 show that the RuIr / TiO2 composite material obtained in Example 1 has characteristic peaks of both the RuIr alloy in Comparative Example 1 and the TiO2 material in Comparative Example 2, indicating that the RuIr alloy is successfully loaded on the TiO2 aerogel.
[0087] The catalytic activity of the catalysts prepared in Examples 1-3 and Comparative Examples 1-2 was evaluated, and the kinetics of the electrocatalytic hydrogen evolution reaction was evaluated by overpotential. The electrochemical test was performed in a conventional three-electrode system, with a platinum wire as the counter electrode and Ag / AgCl as the reference electrode. The catalyst sample was dispersed in an isopropanol aqueous solution of 5wt% Nafion@(Aldrich) and then fixed on a glassy carbon electrode to form a working electrode. Cyclic voltammetry curves (scan rate of 50mV / s) and linear sweep voltammetry curves were obtained in a perchloric acid electrolyte with a concentration of 0.1mol / L at room temperature (25°C).
[0088] Two parameters were used to determine the electrochemical activity: (1) the onset of hydrogen evolution and (2) the peak current at a constant current density (0.01 A*cm -2 ) under the voltage of AgCl, the test results are as follows Figure 4 It can be seen that when the mass of the catalyst is the same, the catalyst prepared in Example 1 has a -2 The corresponding voltage is 55 mV lower than that of Comparative Example 1. The voltage of Examples 2 and 3 is 0.01 A*cm -2 The corresponding voltage is 13 mV higher than that of Comparative Example 1, and Comparative Example 2 has basically no electrochemical activity. Generally speaking, the closer the voltage is to 0 V, the better the electrochemical performance.
[0089] The electrolytic water anode catalyst prepared by the present invention is applied in a PEM electrolysis device, and aerogel is used as a carrier. The network structure characteristics of large particle gaps are conducive to the dispersion of precious metal atoms and improve the atomic utilization rate. At the same time, a large number of defects / vacancies will significantly weaken the binding energy of O* relative to OOH*, thereby reducing the energy consumption in the conversion process from O* to OOH*, reducing the oxygen evolution overpotential, and thus significantly improving the OER activity and current density. In addition, the acid resistance of TiO2 itself can inhibit the agglomeration of precious metal nanoparticles, which is conducive to improving the dispersibility of the RuIr alloy obtained by calcination after impregnation. The rutile phase TiO2 obtained after calcination also has a certain conductivity, which is conducive to the transfer of electrons between catalysts and the progress of the electrolysis reaction.
[0090] Aerogel is also called dry gel. After most of the solvent inside the gel is removed, the mass is greatly reduced. The gas is used as a medium to replace the solvent and fill the spatial network structure of the gel. At this time, the surface of the substance is still solid. The substance formed in this way is dry gel, that is, aerogel.
[0091] The present invention adopts the noble metal Ir as the main alloy element selection, and uses the noble metal Ir and one or more of Ru, Pt and Rh to form an alloy, thereby changing the coordination environment of the metal active center, adjusting the electronic structure, affecting the binding energy between the intermediate and the active center, and thus improving the OER activity and stability.
[0092] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. An alloy-supported conductive aerogel catalyst, characterized in that: The invention comprises a substrate and a precious metal loaded on the substrate, wherein the substrate adopts conductive aerogel, the loading mass ratio of the precious metal on the substrate is 1-20%, the precious metal comprises precious metal A and precious metal B, the molar ratio of the precious metal A to the precious metal B is 1-9:1; the precious metal A is Ir, and the precious metal B comprises one or more of Ru, Pt and Rh.
2. The method for preparing the alloy-supported conductive aerogel catalyst according to claim 1, characterized in that: The following steps are involved: Step S1, dissolving a precursor of precious metal A and a precursor of precious metal B in ethanol, then adding a sodium citrate solution to the mixture, and ultrasonically treating the obtained solution to obtain a solution Y1; Step S2, immersing the conductive aerogel in the solution Y1, then heating and evaporating all the solvent to obtain a wet gel, transferring the obtained wet gel to a porcelain boat, placing it in a tubular furnace, and calcining it at a heating rate of 3-8°C / min in a hydrogen-argon mixed atmosphere, and collecting the obtained black product; Step S3, removal of impurity ions: centrifugally washing the black product obtained in step S2 with deionized water until the conductivity of the washing water is lower than 5 μS / m, so as to remove excess impurity ions; Step S4, catalyst drying: the solid sample washed in step S3 is placed in a vacuum drying oven at 50-80° C. and heated for 12-24 hours to obtain a finished catalyst.
3. The method for preparing the alloy-supported conductive aerogel catalyst according to claim 2, characterized in that: In step S2, the conductive aerogel includes one of TiO2 aerogel, graphene aerogel and biomass carbon aerogel.
4. The method for preparing the alloy-supported conductive aerogel catalyst according to claim 2, characterized in that: The ultrasonic treatment time in step S1 is 10-30 minutes, and the ultrasonic power is 800-1000W; The sodium citrate solution is dissolved and diluted at 2-10 times the weight of the sodium citrate solid, and the ratio of sodium citrate solid added is 10-15 times the total weight of the precious metal compound precursor.
5. The method for preparing the alloy-supported conductive aerogel catalyst according to claim 2, characterized in that: In step S2, the conductive aerogel is immersed in solution Y1 for 6-24 hours; the temperature for heating to evaporate the solvent is 70-90°C, and the heating time is 4-8 hours; the heating temperature of the tubular furnace during calcination is 300-500°C, and the heating time is 2-6 hours.
6. The method for preparing the alloy-supported conductive aerogel catalyst according to claim 3, characterized in that: The preparation of the TiO2 aerogel comprises the following steps: (1) Tetrabutyl titanate Ti(OBu)4, ethanol EtOH and glacial acetic acid CH3COOH are mixed uniformly in a molar ratio of 1: 5-15: 0.2-1 to form a solution Y2; (2) mixing H2O, EtOH and CH3COOH in a molar ratio of 1-5:2-10:1 to form a solution Y3; (3) Slowly add solution Y2 to solution Y3 at a rate of 0.5-2 mL / min, with the volume ratio of solution Y2 to solution Y3 being 0.5-2:1; (4) Adding formamide DMF to the mixed solution obtained in step (3), wherein the molar ratio of Ti(OBu)4 to DMF is 1:0.01-0.2, stirring, and placing in a water bath at a constant temperature to obtain a TiO2 wet gel, and further condensing the obtained TiO2 wet gel at room temperature; (5) Solvent replacement process of gel: the gel condensed in step (4) is placed in a water bath, during which EtOH is replaced. The gel is taken out and immersed in a mixed solution of EtOH and tetraethyl silicate (TEOS) for surface modification. The gel is then immersed in n-hexane to replace the solvent and unreacted products in the gel. (6) The gel is transferred into a beaker, which is wrapped with tin foil and dried in a drying oven at normal pressure using a gradient temperature increase system. After cooling, TiO2 aerogel is obtained.
7. The method for preparing the alloy-supported conductive aerogel catalyst according to claim 6, characterized in that: The stirring time in step (4) is 10-60 minutes, the temperature of the water bath is 20-40° C., the constant temperature standing time is 1-6 hours, and the further condensation time is 6-24 hours.
8. The method for preparing an alloy-supported conductive aerogel catalyst according to claim 6, characterized in that: The temperature of the water bath in step (5) is 30-50°C, the gel is placed in the water bath for 12-36 hours, the number of ethanol replacements is 3-5 times, the volume ratio of EtOH to TEOS during replacement is 1:2-5, the water bath heating temperature range is 50-80°C, and the immersion time is 6-24 hours.
9. The method for preparing an alloy-supported conductive aerogel catalyst according to claim 6, characterized in that: The gradient temperature rise system in step (6) is 50°C, 80°C, 100°C, 120°C, 140°C and 160°C, with each temperature maintained for 30-60 minutes.
10. The use of the alloy-supported conductive aerogel catalyst according to claim 1, characterized in that: The catalyst is used as an anode catalyst for electrolyzing water to electrolyze water.
Citation Information
Cited By
PEM electrolyzed water anode catalyst and preparation method and application thereof
CN121204723A